Economic Growth in Indonesia: Dynamics of Poverty, Unemployment, and Health Budgets - Sulaeman, Maman; Suharno, Suharno; Ahmad, Abdul Aziz (Agregat: Jurnal Ekonomi dan Bisnis, 2024)
Even with Indonesia's impressive recent economic expansion, issues including poverty, unemployment, health care spending, housing, education, and labor productivity continue to be serious problems. International organization databases, government reports, academic publications, national statistics agencies, and academic publications are some of the sources that can be used for secondary quantitative data analysis encompassing 34 provinces from 2018 to 2022. The results show that unemployment, poverty all have a detrimental effect on economic growth. On the other hand health budget allocations all have a favorable impact. The study concludes that while investments in health budgets positively influence growth by enhancing human capital and, poverty, unemployment negatively impact economic growth. This study's conclusion about the correlation between the variables can offer insightful information to practitioners across a range of fields and public policy.